The cascade of HIV care among refugees and nationals in Nakivale Refugee Settlement in Uganda - O’Laughlin, KN; Kasozi, J; Rabideau, DJ; Parker, RA; Mulogo, Edgar Mugema; Faustin, ZM; Greenwald, KE; Doraiswamy, S; Walensky, RP; Bassett, IV (HIV medicine, 2017)
Objectives Refugees living in Uganda come from HIV-endemic countries, and many remain in refugee settlements for over a decade. Our objective was to evaluate the HIV care cascade in Nakivale Refugee Settlement and to assess correlates of linkage to care. Methods We prospectively enrolled individuals accessing clinic-based HIV testing in Nakivale Refugee Settlement from March 2013 to July 2014. Newly HIV-diagnosed clients were followed for 3 months post-diagnosis. Clients underwent a baseline survey. The following outcomes were obtained from HIV clinic registers in Nakivale: clinic attendance (‘linkage to HIV care’), CD4 testing, antiretroviral therapy (ART) eligibility, and ART initiation within 90 days of testing. Descriptive data were reported as frequency with 95% confidence interval (CI) or median with interquartile range (IQR). The impact of baseline variables on linkage to care was assessed with logistic regression models. Results Of 6850 adult clients tested for HIV, 276 (4%; CI: 3–5%) were diagnosed with HIV infection, 148 (54%; CI: 47–60%) of those were linked to HIV care, 54 (20%; CI: 15–25%) had a CD4 test, 22 (8%; CI: 5–12%) were eligible for ART, and 17 (6%; CI: 3–10%) initiated ART. The proportions of refugees and nationals at each step of the cascade were similar. We identified no significant predictors of linkage to care. Conclusions Less than a quarter of newly HIV-diagnosed clients completed ART assessment, considerably lower than in other reports from sub-Saharan Africa. Understanding which factors hinder linkage to and engagement in care in the settlement will be important to inform interventions specific for this environment.
Keywords: Care continuum; Cascade of care; HIV; Refugee; Sub-Saharan Africa